Endogenous T-Cell Therapy: Clinical Experience. Issue 6 (November 2015) - Yee, Cassian; Lizee, Greg; Schueneman, Aaron J.
Abstract : Abstract: Adoptive cellular therapy represents a robust means of augmenting the tumor-reactive effector population in patients with cancer by adoptive transfer of ex vivo expanded T cells. Three approaches have been developed to achieve this goal: the use of tumor-infiltrating lymphocytes or tumor-infiltrating lymphocytess extracted from patient biopsy material; the redirected engineering of lymphocytes using vectors expressing a chimeric antigen receptor and T-cell receptor; and third, the isolation and expansion of often low-frequency endogenous T cells (ETCs) reactive to tumor antigens from the peripheral blood of patients. This last form of adoptive transfer of T cells, known as ETC therapy, requires specialized methods to isolate and expand from peripheral blood the very low-frequency tumor-reactive T cells, methods that have been developed over the last 2 decades, to the point where such an approach may be broadly applicable not only for the treatment of melanoma but also for that of other solid tumor malignancies. One compelling feature of ETC is the ability to rapidly deploy clinical trials following identification of a tumor-associated target epitope, a feature that may be exploited to develop personalized antigen-specific T-cell therapy for patients with almost any solid tumor. With a well-validated antigen discovery pipeline in place, clinical studies combining ETC with agents that modulate the immune microenvironment can be developed that will transform ETC into a feasible treatment modality.